PENGARUH PENDIDIKAN KESEHATAN METODE PERMAINAN REDI (RODA EDUKASI DAN INSPIRASI) TERHADAP PENGETAHUAN REMAJA PUTRI UNTUK MENCEGAH SEKS PRANIKAH - Pratiwi Ningsih; Sri Utami; Nurul Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Premarital sex behavior can cause a variety of negative effects on teenagers as unwanted pregnancies and abortion. Lack of knowledge can affect teenagers knowledge about the effect and prevent premarital sex. Another factors that can affect adolescents knowledge is health education. This study aims to determine the knowledge of young women through the REDI game method (Wheel of Education and Inspiration) to prevent premarital sex in the Labuh Baru Barat Payung Sekaki Pekanbaru District. This research used quasy experiment design with the non-equivalent control group. The sample of this research was 34 respondents taken based on the inclusion criteria using purposive sampling technique, divided into experimental group and control group. The score of knowledge was measured by using a questionnaire that has been tested for validity and reliability. The analysis used was univariate and bivariate analysis using Wilcoxon test, dependent t-test, and Mann Whitney test. The results showed a significant increase in teenagers knowledge about premarital sex prevention after being given health education through the REDI game method (Wheel of Education and Inspiration) with the p-value (0.000) < alpha (0,05). The results show that health education through the REDI game method (Wheel of Education and Inspiration) is effective to increase teenagers knowledge for premarital sex prevention. The result of this study can be an alternative for nursing intervention to increase adolescents knowledge to premarital sex prevention.  Keywords: Health education, knowledge, premarital sex, redi game method, teenagers